The Effects of Mompyeogi Movement Exercise on Body Skin Temperature - Widyaatmadja, Swanny T; Young-Duk, Kim (Nurse Media Journal of Nursing, 2019)
Background: Spine stretching and flexibility exercise is introduced by the group of Mompyeogi movement exercise ('mom' as body and 'pyeogi as stretching) that is growing in the Republic of Korea. Although it does not move as fast as an aerobic exercise, the benefit of body organ stretching movement position on this movement exercise can be perceived by Mompyeogi participants.Purpose: This study aimed to investigate the effects of Mompyeogi movement exercise on the alteration of body skin temperature.Methods: A pre-post experimental study was carried out to 20 participants who were divided into two groups: male and female. Each group was assigned to do either normal breathing (chest respiration) or deep breathing (abdominal respiration) when performing Mompyeogi movement exercise. Body skin temperatures were measured a couple of times before, during, and after the exercise using thermal infrared cameras. The collected data were analyzed descriptively in frequency and percentage.Results: Results showed that Mompyeogi movement exercise combined with deep abdominal breathing methods increased body skin temperature. Participants who were in low group temperature (t<33Â°C), underweight, and had normal body mass index showed an increased body skin temperature after the exercise. On the other hand, participants who were in the group age of 60-74 years old performing normal chest respiration showed a stable body skin temperature after the exercise.Conclusion: Stretching organ as a part of basic Mompyeogi movement exercise combined with deep abdominal breathing increased the body skin temperature. Future research of Mompyeogi movement exercise needs to explore a self-healing effort as a preventing and promoting programs contributed to holistic nursing practice.Â